From Classroom to Codex: The Materiality of the Minor Declamations. - Golubović, Nikola (Classical Philology, 2025)
This article proposes a reconstruction of the material history of the Minor Declamations ascribed to Quintilian. Going off of two subscriptions preserved in the textual tradition, it argues that what started as a cache of class notes was eventually copied to a new medium, approximately three to five parchment codices, and from there to a two-volume declamatory corpus whose structure is preserved in the surviving manuscripts. The first volume of this corpus was lost before the archetype of the extant tradition was copied. The article concludes by discussing the implications that the fate of the Minor Declamations carries for the study of other utilitarian texts.